The psychology of Paralympic athletes: A bibliometric analysis. - Öner, C. (International Journal of Disabilities Sports and Health Sciences, 2023)
Comprehending the paralympic athletes' psychology is paramount due to their distinctive challenges. Sports can be a facilitator, strengthening emotional well-being, coping mechanisms, and self-confidence and fostering resilience, yet internal stressors can undermine their mental health. It is crucial to elucidate the publications' fundamental components displaying a growing trend within this framework. Hence, this study aims to explore a comprehensive bibliometric analysis of paralympic athletes' psychology. The Web of Science database was analyzed for publications from 1992 to Sept. 1, 2023, across Social Sciences Citation, Science Citation Index Expanded, Emerging Sources Citation, and Arts & Humanities Citation indexes. Among these, 263 articles were integrated, encompassing 13 categories of sports, psychology, and sociology. This study utilized VOSviewer 1.6.19 to investigate citation and bibliometric coupling analysis and provided keywords, occurrence, and co-citation analysis. The findings indicate that 2022 witnessed the most cited publications, comprising 34 articles. Further findings revealed that David L. Mann is the top-cited author, the British Journal of Sports Medicine is the top-cited journal. Bibliometric coupling results underlined Psychology of Sport and Exercise, Loughborough University, and England, with the highest total link strength, respectively, as journal, institution, and country. Regarding study results, the most notable keyword clusters are sports, paralympic games, paralympic, paralympics, disability, and paralympic athletes. Finally, the top terms featured in abstracts were game, impairment, person, difference, program, and participation. Consequently, distinguished writers, organizations, and nations not only engage in vigorous interactions within their respective domains but also maintain robust and meaningful connections with one another.